THE ROLE OF DIDACTIC GAMES IN MAKING STUDENTS INTERESTED IN MATHEMATICS - Raximov Shahriyor Normurod o‘g`li; Mamatova Durdona Norbek qizi (Zeta Repository, 2023)
In this article, through didactic games in mathematics lessons in elementary school, the quality and effectiveness of education in the educational process is improved, the content and meaning of mathematical concepts are deeply and clearly presented, the interest of primary school students in mathematics is discussed, methods of improvement are mentioned.